Pengaruh Kedisiplinan Dan Pendampingan Belajar Orang Tua Terhadap Prestasi Belajar Ipa Siswa Kelas Atas Sd N 01 Jatisawit 2015/2016 - , Iswantoko; , Dr. Achmad Fathoni, M.Pd (2016)
This study aims to determine: (1) the effect of the discipline of student learning on student achievement in science subjects upscale SD N 01 Jatisawit (2) the effect of facilitation of learning of parents on student achievement in science subjects upscale SDN 01 Jatisawit (3) influence the discipline of learning and mentoring of parents on student achievement in science subjects upscale SD N 01 Jatisawit. This type of research is quantitative research. Subjects in this study are students upscale SD N 01 Jatisawit year 2015/2016. The data collection technique used was a questionnaire, documentation. Mechanical testing instruments used are validity and reliability testing. Techniques used prerequisite test is the test of normality and linearity test. Data analysis technique used is multiple regression analysis, t-test, f, coefficient of determination and looking for the contribution given. The first hypothesis of the calculation results obtained t> t table (4.687> 2.005) and sig <0.05 (0.000 <0.05). From the calculation of the second hypothesis is obtained t> t table (2,737> 2,005) and sig <0.05 (0.008 <0.05). The third hypothesis of the calculation results obtained Fhitung> F table (71.895> 3.15) and sig <0.05 (0.000 <0.05). So that the conclusions of this study are (1) Discipline learning effect on learning achievement grade science students on SD N 01 Jatisawit (2) Mentoring learn parental influence on learning achievement grade science students on SD N 01 Jatisawit (3) Disciplinary learning and mentoring learn the parents influence the learning achievement grade science students on SD N 01 Jatisawit.